Voice converter on android - Y, Lee W; Murli, Norhanifah; Wahid, Norfaradilla; A Hamid, Rahayu; Othman, Mohd Hilmi (IOP Publishing, 2018)
Voice Converter is an application developed for Android mobile platform that can help user to change his voice the way he likes. Existing voice changer mobile application provides the functions for users to change their voice into the voice of limited preset templates, this cannot see to the needs of film or animation producers, because the templates are limited and the uniqueness of the production cannot be secured. With the Voice Converter mobile application, film or animation producers can easily have access to a number of sound models that can be used to convert audio files which can be used in production later. Besides that, film makers can custom the sound of the conversion by inputting desired values of playback rate to change the audio sound in the way they would like to. The application uses speaker and microphone of the phones to play and record audio. For the recording process, the ‘MediaRecorder’ APIs is used to allow the device to capture audio, save the audio and play it back. The recordings captured can be converted into various sound models and also a model with custom parameters. The SoundPool Library is adopted to alter the playback rate of the audio. A mobile application named Voice Converter which is compatible for Android platforms is successfully developed. The functions of the application include recording and saving audio, converting input audio into existing template sound and converting recorded audio with custom parameter